APE1 and XRCC3 polymorphisms and myocardial infarction - (:unkn) unknown (International Institute of Anticancer Research, 2008)
Background: In most cells, DNA is regularly damaged by mutagens. Different DNA repair mechanisms operate on specific types of damaged DNA. When DNA damage resulting from free radicals is not repaired, it might lead to deteriorated gene expression, the development of a number of diseases such as cancer, diabetes, vascular diseases, and aging. In the present study, APE1 and XRCC3 gene polymorphisms were investigated in patients with myocardial infarction. Materials and Methods: Forty-five first time elective coronary artery bypass grafting (CABG) patients with cardiopulmonary bypass (CPB) and 40 healthy individuals were studied. Gene polymorphisms were determined by a polymerase chain reaction-restriction fragment length polymorphism method. Results: For the APE1 gene, the AG genotype was significantly higher in the patient group than in the control group. The patient group had significantly more G carriers but there was no statistically significantly difference between patient and control groups the A allele. The XRCC3 TT genotype was found to be significantly more frequent in the patient group than it was in the control group. Conclusion: The results of our study suggested that the XRCC3 gene TT genotype and the APE1 gene AG genotype might increase the risk of myocardial infarcts.
Keywords: Coronary artery disease; DNA damage; DNA repair; Gene; Oxidative stress